Meta-Analysis: The Effect of Learning Models on Students' Scientific Literacy - Nici Jumatul FItri, Nici; Kartika, Puput; Lutfiana , Gita (Universitas Negeri Padang, 2023)
In the 21st century, where technology and science are developing rapidly, scientific literacy is very important. Technology and scientific literacy in particular can help improve the quality of a country's education. By collecting 20 research results, this meta-analysis research aims to summarize research findings regarding the influence of learning models on students' scientific literacy abilities. This research aims to find out: the average effect size (ES) of which type of learning model has the largest effect size at the level of education, and which learning model has the most influence on students' scientific literacy. The results of the research show that the average ES is 1.21, which shows that the use of learning models has a significant impact on students' scientific literacy. The type of learning model most often used to increase students' scientific literacy is the Problem-Based Learning model with an average ES of 1.28. The Problem-Based Learning model is more influential at the high school education level with an average ES of 1.58 and on science material of 1.30 with an effect size in the high category.